El desarrollo de las competencias matemáticas en cuarto grado de la escuela de educación básica particular Amauta periodo 2024-2025. - Cañar Calva, Gloria Mercedes (2025)
This study emphasizes the significance of incorporating didactic methodologies to enhance the development of mathematical competencies. Specifically, the Mini Arc methodology was analyzed as an effective didactic tool for fostering mathematical skills in children. The objective of this research is to examine how the implementation of didactic methodologies influences the development of mathematical competencies in fourth-grade students at Amauta Private School during the 2024–2025 academic year. The study involved a sample of 16 fourth-grade students and one mathematics teacher. Using a mixed-methods approach—qualitative, quantitative, and descriptive—the research focused on the relationship between two key variables: didactic methodologies and mathematical competencies. Data collection instruments included a diagnostic questionnaire, a student survey, and a teacher interview. The findings revealed that fourth-grade students face challenges in developing mathematical competencies, particularly in numerical patterns, geometric figures, and basic operations such as addition, subtraction, multiplication, and division. These results underscore the necessity of diversifying instructional methodologies to promote active student participation, as traditional teaching methods currently dominate the classroom. The research concludes that the Mini Arc methodology facilitates the development of cognitive skills, enhances learning, and strengthens mathematical competencies in children. Moreover, specific guidelines were proposed to address the identified challenges, demonstrating that the Mini Arc methodology can significantly improve mathematical competency development when effectively implemented